E-Government concept: A holistic and eclectic framework - Soares, Delfina de Sá (2013)
Over the last few years, many different definitions for the e-government term have appeared in the literature. This diversity of definitions created a conceptual multiplicity and divergence. While being understandable, taking into consideration the newness of the e-government field, this may be prejudicing the e-government research and development. The aim of this chapter is to contribute to the clarification of the e-government concept, by providing a framework that hopefully will help to understand its boundaries and main constituents, as well as the way in which many of the different related terms found in the literature, can be further articulated. The framework put forward in this chapter is based on a generic model of a democratic government system. Building on that model, six main spaces, where Information Technologies (ITs) can be deployed, are identified and discussed. The use of IT in all those spaces contributes to the overall development of a country’s e-government reality and maturity. By suggesting and arguing for a comprehensive, holistic and eclectic vision of e-government, this framework provides a basis for achieving more sustained e-government research and development efforts.